MAGGIE and the MOONBIRD - Balen, Katya; Phuc, Pham Quang (London : BLOOMSBURY EDUCATION, 2021)
"Margot wants her parents to take her birdwatching like they promised but they're too busy and she ends up at the zoo with her auntie and her annoying cousins. There, she sees a strange bird and takes one of its beautiful silver feathers home. Little does she know, that this is the start of a magical adventure in the moonlight"--Publisher's description.
Keywords: Children's stories; Animal -- Fiction; Fantasy -- Fiction